Review of Spousal Communication and the Increasing Rate of Divorce in Nigeria Society - Joy Collins-Dike (Matondang Journal, 2025)
The home is frequently referred to be the fundamental building block of greater society. Hence, when the house is peaceful, so is society. The primary goal of this study was to determine how spousal communication affected divorce proceedings and family stability in Nigeria. The library research method was used for this study. This method allowed the researcher review secondary literatures and analyzed the positions of scholars to derive a conclusion. Symbolic interactionism theory formed the theoretical basis of the study and argues that interpersonal communication among people is the most humanizing activity engaged daily by people and is needed for daily sustenance of relationships. The paper concludes that divorce can most likely occur when two partners have lost communication or have exhausted all communication links and decided that the union should not go further. While some divorce cases might have other triggers such as abuse or other forms of unresolved conflicts, this paper posit that almost all divorce cases have communication effect whether directly or indirectly hence a couple with a high level of marital communication (without secrecy) stands a greater chance of staying longer together. It was argued also in this paper that money and financial communication is a key consideration in marriages if the couples want to enjoy bliss and avoid divorce. This paper recommends that couples should engage in constant communication to share their problems as they arise and ensure to deal with it from the foundation. Also, when choosing a life partner, intending couples need to ensure that the partner is someone they can easily communicate with on a balanced level where feedback is gotten in due time (almost immediately and not coerced). Furthermore, the issue of family finance should be discussed at length to avoid subsequent financial disputes due to lack of accountability and excessive secrecy.